'It's more than a prop': Professional development session strategies as sources of teachers' self-efficacy and motivation to teach outside the classroom. Issue 3 (27th May 2019) - Glackin, Melissa
ABSTRACT: This paper discusses findings from a small-scale empirical exploration of how professional development (PD) programme session strategies influence secondary science teachers' practice. It draws on a series of session questionnaires, semi-structured interviews and lesson observations from six secondary science teachers participating in a 2-year outdoor teaching PD programme in England. This paper explores session strategies as sources of self-efficacy resulting in practice change. It is argued that strategies most influential are those that combined several self-efficacy sources. However, alongside self-efficacy, the motivating role strategies play are important to the successful outcome of PD programmes.